Analysis of Students' Design Thinking in Information Technology Innovation - Indriaturrahmi, Indriaturrahmi; Prayogi, Saiful; Asy'ari, Muhammad; Samsuri, Taufik (Universitas Pendidikan Mandalika, 2023)
This study delves into the design thinking characteristics among students in the field of information technology innovation, examining their competencies within the context of the Information Technology Education program at Mandalika University of Education - Indonesia. Employing an exploratory descriptive research design, the research focuses on 30 students, utilizing the Design Thinking Scale to assess six crucial dimensions: comfort with uncertainty and risks, human-centeredness, mindfulness of the process and impacts on others, collaborative work with diversity, orientation to learning by making and testing, and confidence and optimism to use creativity. The findings reveal a comprehensive understanding of the nuanced aspects of students' design thinking capabilities, indicating areas for improvement. Notably, students exhibit discomfort with uncertainty and risks, signaling a need for interventions to enhance resilience and adaptability. Human-centeredness, collaborative work with diversity, and mindfulness to the process receive